Faktor-Faktor Yang Mempengaruhi Perubahan Identitas Kota di Kawasan Kota Tua Muara Tebo Kabupaten Tebo Provinsi Jambi - Adrian, Moh.; Setioko, Bambang (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
The existence of the town can not be separated from its identity, that all the city has a different identity, both positive and negative. The identity of a city is unique conditions and characteristics that distinguish it from other cities. Kota Tua Tebo has an identity with the history of its existence, but because of the policy direction of the development of the City Tebo, the region began to change the identity of the city that are currently physically known only as the old market area and non-physical only a region that is not known as Tebo city beginning. The approach used in this study is a quantitative deductive rationalistic by using descriptive analysis of empirical and statistical factor analysis. Factors affecting the change of identity of the city in the Old Town area Tebo Tebo dtemukan 2 (two) factors, namely physical (organization of space) and non-physical factors (activity and policy space), and 10 (ten) identity factor town. Recommendation is to pay attention and consider each development policy based on the condition of attachment, attention to the development of the city in the future and visual character of the area.